2016
DOI: 10.1186/s12888-016-0829-2
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and its association with psychological and somatic health problems among Czech, Russian and U.S. adolescents

Abstract: BackgroundLoneliness is common in adolescence and has been linked to various negative outcomes. Until now, however, there has been little cross-country research on this phenomenon. The aim of the present study was to examine which factors are associated with adolescent loneliness in three countries that differ historically and culturally-the Czech Republic, Russia and the United States, and to determine whether adolescent loneliness is associated with poorer psychological and somatic health.MethodsData from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
82
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 60 publications
14
82
1
1
Order By: Relevance
“…These mixed findings have been confirmed in some previous studies (6,9). In agreement with previous studies (7)(8)(9), this study found that peer victimization, having fewer close friends, and lack of parental or guardian support were associated with loneliness. Peer or bullying victimization may be related to loneliness because of its effects on poor friendship formation (7,21).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These mixed findings have been confirmed in some previous studies (6,9). In agreement with previous studies (7)(8)(9), this study found that peer victimization, having fewer close friends, and lack of parental or guardian support were associated with loneliness. Peer or bullying victimization may be related to loneliness because of its effects on poor friendship formation (7,21).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies (7)(8)(9), this study found that peer victimization, having fewer close friends, and lack of parental or guardian support were associated with loneliness. Peer or bullying victimization may be related to loneliness because of its effects on poor friendship formation (7,21). The finding that having a close friend was a protective factor against loneliness may be explained by the important role of close friends in providing social interaction and support (7).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations